Counter-narratives: The Importance of Our Stories in Adult Educational Research - Cindy Peña; Esther S. Pippins; Sonia Rey Lopez; Humberto de Faria Santos (Adult Education Research Conference, 2022)
We propose the development of counter-narratives as a research methodology in adult education to increase the visibility of Ph.D. professionals and merit the educational equity this field aspires to reach.
Keywords: Counter-narratives; methodology; adult educational research; testimonios; feminisms